2019
DOI: 10.1080/1828051x.2018.1553507
|View full text |Cite
|
Sign up to set email alerts
|

Determination of carcase yield, sensory and acceptance of meat from male and female pigs with dietary supplementation of oregano essential oils

Abstract: 2019) Determination of carcase yield, sensory and acceptance of meat from male and female pigs with dietary supplementation of oregano essential oils ABSTRACTThe aim was to determine the dietary supplementation of oregano essential oil (OEO) to male and female pigs on carcase performance, sensory characteristics and consumer acceptability of meat. A total of 48 pigs (Landrace  Yorkshire) of 18.5 ± 5.4 kg live weight were randomly allotted into one of four experimental diet groups each containing 12 pigs. Each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(47 reference statements)
2
0
0
Order By: Relevance
“…In goats, carcass weight was different from the control group by providing OEO plus cobalt in the diet, attributed to consumption stimulation [52]. In studies where a positive effect of OEO has been reported, it is considered that it improves nutrient absorption [53]. Ünal and Kocaba ǧli [15] mention that the hot carcass yield is related to the results obtained in the productive performance, similar to the present study, where hot carcass yields were similar between treatments.…”
Section: Discussionsupporting
confidence: 81%
“…In goats, carcass weight was different from the control group by providing OEO plus cobalt in the diet, attributed to consumption stimulation [52]. In studies where a positive effect of OEO has been reported, it is considered that it improves nutrient absorption [53]. Ünal and Kocaba ǧli [15] mention that the hot carcass yield is related to the results obtained in the productive performance, similar to the present study, where hot carcass yields were similar between treatments.…”
Section: Discussionsupporting
confidence: 81%
“…The extensive spice odor reflects the ability of muscle tissues to absorb these plant polyphenols. Similar results were obtained in several studies evaluating the effect of dietary oregano plants and their essential oil on meat sensory evaluation (Kirkpinar et al, 2014;Janacua-Vidales et al, 2019). Results for the attribute oxidation odor agreed with the previous findings for lipid and protein oxidation (Tables 4 and 5).…”
Section: Sensory Evaluationsupporting
confidence: 90%